ИССЛЕДОВАНИЕ АКТИВНОСТИ ЯДРА СЕЙФЕРТОВСКОЙ ГАКТИКИ NGC 7469 ЗА ПЕРИОД НАБЛЮДЕНИЙ С1990-2008 ГГ. - Уголькова, Л. С.; Артамонов, Б. П. (Одеські астрономічні публікації, 2011)
We combine many published photometrical observations of the Seyfert Galaxy (SG) NGC 7469 and also new results from Hubble Space Telescope which can be used for future research of some properties of the activity of the nuclear of the SG. A drift of the activity maximum from 1997 to 1998 is observed with an increased of the wave length similarly to some blazars in radio range. Analyzing the surface photometry according to data obtained both at the Maidanak observatory and HST data an intensity asymmetry at the SG central region image is observed at different periods. The existence of a second component might be supposed. The radius of the active region itself inside the SG kernel is 40-50 parsec.